2012
DOI: 10.3109/10428194.2012.722218
|View full text |Cite
|
Sign up to set email alerts
|

Synergism between fibronectin and transforming growth factor-β1 in the production of substance P in monocytes of patients with myelofibrosis

Abstract: Substance P (SP), also considered a proinflammatory cytokine, as well as others such as transforming growth factor-β1 (TGF-β1) and interleukin-1 (IL-1), and the extracellular matrix protein fibronectin (FN) have been associated with the pathophysiology of myelofibrosis. SP is encoded by the TAC1 gene. The relationships among SP, TGF-β1, IL-1 and FN are poorly understood. This study determined the mechanisms for concomitant production of IL-1, TGF-β1 and SP and also determined the synergistic role of FN in SP r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
8
0
3
Order By: Relevance
“…Therefore, considering that our results are consistent with these previous studies, it is likely that SP plays an important role in many kinds of tissue fibrosis. Other studies have shown that SP, through NK‐1R, contributes to the progression of myelofibrosis . In addition, NK‐1R antagonists have been shown to protect mice from cytokine‐mediated liver injury and reduce hepatocyte apoptosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, considering that our results are consistent with these previous studies, it is likely that SP plays an important role in many kinds of tissue fibrosis. Other studies have shown that SP, through NK‐1R, contributes to the progression of myelofibrosis . In addition, NK‐1R antagonists have been shown to protect mice from cytokine‐mediated liver injury and reduce hepatocyte apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that SP, through NK-1R, contributes to the progression of myelofibrosis. (27) In addition, NK-1R antagonists have been shown to protect mice from cytokine-mediated liver injury and reduce hepatocyte apoptosis. (8,28) In support of these previous findings, our results introduce the novel concept that NK-1R antagonists decrease liver fibrosis in Mdr2 -/mice, reducing biliary damage and increasing the senescence of HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…82 One study showed that fibronectin can activate monocytes in patients with MF via increased monocytic production of substance P, a proinflammatory cytokine. 83 …”
Section: Structural Proteins Of the Ecm And Their Relevance To And Romentioning
confidence: 99%
“…Умеренное повышение плазменной концентрации TGF-β1 отмечено у мышей (линия Gata1 low ). Десятикратное повышение содержания TGF-β1 в мегакариоцитах отмечалось как у животных, так и у человека [13].…”
unclassified
“…У мышей (линия Gata1 low ) на фоне повышения содержания TGF-β1 установлена активация Hedgehog и р53 сигнализации в селезёнке и костном мозге. Авторы считают, что ингибирование TGF-β1 сигнального пути у мышей (линия Gata1 low ) способствует снижению выраженности фиброза костного мозга на фоне замедления кроветворения в селезёнке [13].…”
unclassified